Bir ekonomi bürokratının portresi:Mustafa Şeref Özkan - Şabudak, Özcan (My University, 2004)
Bu çalışmada Mustafa Şeref Özkan'ın siyasi yaşamı boyunca bir süreklilik arz eden çalışmaları derlenerek sahip olduğu iktisadi görüşler ele alınmıştır. Tez'in ilk bölümünde Mustafa Şeref Özkan'ın hayatı ve hakkında söylenenler ile onun kişiliği ve vasıfları ortaya konulmaya çalışılmıştır.İkinci bölümde I. Dünya Savaşı yıllarında bulunduğu Ticaret ve Ziraat Nazırlığı esnasındaki çalışmaları ele alınmış olup son bölümde ise Cumhuriyet yıllarında kısa bir süre bulunduğu ''İktisat Vekilliği'' sırasında yaptığı çalış- malarla, 1930'lu yıllardaki Devletçilik uygulamalarının altyapısının oluşumundaki katkıları anlatılmıştır.

In this thesis, Mustafa Şeref Özkan's academic Works are collected and his a ideas regarding economics are taken into consideration. In the first chapter, Mustafa Şeref Özkan's life, comments about his life and personality are tried to be taken up. In the second chapter, his works and experiences during his tenure as the minister of commerce and agriculture are focused. In the final chapter, his accounts during his short tenure as the minister of economics and his contributions in paving the ground for the infrastructure of the applications of statism in 1930's. CV ( Curriculum Vitae ) I was born in İstanbul in 1973. After finishing his primery and elemantary education in şişli and şirinevler respectively, he completed his high school education ship machines at deparment in İstanbul Denizcilik Lisesi. Later on, he graduated from history deparment, İstanbul university.
Keywords: Ekonomi_Tarih_Türkiye; Özkan, Mustafa Şeref, 1885_1938